AMPK induced memory improvements in the diabetic population: A case study. Issue 6 (November 2018) - Halikas, Alicia; Gibas, Kelly J.
Abstract: Diabetics in mid-life carry a 1.5 times higher risk of developing Alzheimer's disease than those diagnosed with diabetes (T2D) later in life [1 ]. Recent research points to accelerated cognitive decline within a range of 20%–50% for middle-aged diabetics as compared to non-diabetic populations [2, 3 ]. Metabolic syndrome (MetS), a type 2 diabetes (T2D) precursor, is also linked to MCI and AD pathologies via hypo-metabolic brain circuitry that inhibits glucose metabolism and attenuates cognitive function [4 ]. Dysregulation of intracellular and extracellular signaling as mediated by the mTOR and AMPK pathways is the result. These critical nutrient sensing pathways modulate epigenetic shifts in the genome by channeling fuel substrates either towards mitochondrial fatty acid oxidation (AMPK) or cytosolic glycolysis and substrate level phosphorylation (mTOR) [5 ]. This case study was designed to examine the link between peripheral insulin resistance and early stage memory loss in a type 2 diabetic male. Reactivating the AMPK pathway via induced and controlled nutritional ketosis combined with high intensity interval training (HIIT) (in order to inhibit mTOR signaling) were primary features of the 10 week intervention. Post intervention results revealed statistically significant reductions in HgA1c, fasting insulin and HOMA-IR (homeostatic model assessment of insulin resistance). Restoring peripheral and hypothalamic insulin sensitivity by way of AMPK activation may restore memory function, improve neuroplasticity, and normalize MetS biomarkers (Demetrius and Driver, 2014; [4, 6 ]).